Experience participating in the American College of Cardiology Quality NetworkTM: paediatric and adult congenital cardiology collaborative quality improvement. (30th October 2018) - Hartwell, Lauren P.; Baker, Annette L.; Jenkins, Kathy J.; de Ferranti, Sarah D.; Saleeb, Susan F.
Abstract: Background: The American College of Cardiology Quality Network enables national benchmarking and collaborative quality improvement through vetted metrics. We describe here our initial experience with the Quality Network. Methods: Quarterly data for metrics pertaining to chest pain, Kawasaki disease, tetralogy of Fallot, elevated body mass index, and others were shared with the collaboratives for benchmarking. National improvement efforts focussed on counselling for elevated body mass index and 22q11.2 testing in tetralogy of Fallot. Improvement strategies included developing multi-disciplinary workgroups, educational materials, and electronic health record advances. Results: Chest pain metric performance was high compared with national means: obtaining family history (90–100% versus 51–77%), electrocardiogram (100% versus 89–99%), and echocardiogram for exertional complaints (95–100% versus 74–96%). Kawasaki metric performance was high, including obtaining coronary measurements (100% versus 85–97%), prescribing aspirin (100% versus 86–99%), follow-up with imaging (100% versus 85–98%), and documenting no activity restriction without coronary aneurysms (83–100% versus 64–93%). Counselling for elevated body mass index was variable (25–75% versus 31–50%) throughout quality improvement efforts. Testing for 22q11.2 deletion in tetralogy of Fallot patients was consistently above the national mean (60–85% versus 54–68%) with improved genetics data capture. Conclusion: The Quality Network promotes meaningful benchmarking and collaborative quality improvement. Our high performance for chest pain and Kawasaki metrics is likely related to previous improvement efforts in chest pain management and a dedicated Kawasaki team. Uptake of counselling for elevated body mass index is variable; stronger engagement among numerous providers is needed. Recommendations for 22q11.2 testing in tetralogy of Fallot were widely recognised and implemented.